The business book - Atkinson, Sam (DK Publishing, 2014)
"An innovative and accessible guide to business, management and commerce Learning about business can be daunting, but The Business Book makes it easier than ever by giving you all the big ideas simply explained. Simple explanations and stylish infographics open up the business world to even the complete novice. The Business Book is the perfect primer to key theories of business and management, covering inspirational business ideas, business strategy and alternative business models. 100 key quotations introduce you to the work of great commercial thinkers, leaders and gurus from Henry Ford to Steve Jobs and to topics spanning from start-ups to ethics. Whether you are a would-be entrepreneur or just have an interest in business, The Business Book is an all-in-one guide to business management, theory and strategy."
Životopisná data
Terminologický slovník
Obsahuje rejstřík
Keywords: podnikání; management; podnikatelé; business; businessmen; populárně-naučné publikace; popular works